ANALISIS EPISTEMOLOGICAL OBSTACLE SISWA SMA PADA MATERI TRIGONOMETRI - Maya Isna Insani; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This research is motivated by the large number of students who experience learning barriers on trigonometry material. The obstacles that often occur in students when solving questions that are not routine such as questions in the form of stories. The purpose of this study is to analyze the epistemological obstacle of high school students on trigonometry material. The method of this research is a descriptive qualitative method with the subject of the study being students of class XI in one of the high schools in West Bandung with 27 students. The instrument used was a test in the form of a description of trigonometric material and interview guidelines. Data analysis techniques used are: Data reduction, data presentation and data verification. The results and discussion of this study is that the epistemological obstacle of high school students on trigonometry material occurs because of the limitations of students when solving non-routine problems. When students are given unusual questions, which are questions in the form of stories, students experience learning obstacles and tend to be unable to solve problems by completing. Students who are given ordinary or easy problems will make students difficult in working on questions in the form of stories. Students should be given problems in the form of problem solving, so students can think critically and will not have difficulties when given questions in the form of stories or problem solving.